An initial molecular signature of Indian isolates of Toxocara - JEEVA, K; CHATTERJEE, N; BERA, A K; MAITI, S; RAM, HIRA; BANERJEE, P S; GOSWAMI, T K; DAS, P J; CHAMUA, J; MILTON, A A P; ARAVIND, M; BHUVANAPRIYA, G; et al. (The Indian Journal of Animal Sciences, 2015)
This communication deals with molecular signature of Toxocara canis, T. cati and T. vitulorum collected from different geographical locations and host assemblages of India. T. vitulorum was collected from cattle, yak and mithun of West Bengal, Arunachal Pradesh and Nagaland, respectively. Isolated parasites were initially identified morphologically before proceeding for molecular characterization. ATP synthase subunit 6 (atp6) gene had a 598 bp stretch which contained both the punctuation codons but was unique in its characteristics due to presence of abbreviated stop codon (T). On the basis of phylogenetic analysis of atp6, 12S and transcribed spacer sequences, three species could be clustered in three different groups. Number of preferred and non preferred codons also varied in between three species of Toxocara of Indian origin. Atp6 gene had abundance in guanine (G) and thymine (T) bases which has also been described as unique characteristic for Neodermata. Restriction profile of transcribed sequences, 5.8S gene and a small fragment of 28S gene could differentiate Indian isolates of Toxocara in two different clades.